2015
DOI: 10.1111/ffe.12364
|View full text |Cite
|
Sign up to set email alerts
|

A relative crack opening time correlation for corrosion fatigue crack growth in offshore structures

Abstract: A considerable amount of research has been carried out on the prediction of mean stress effects on fatigue crack growth in structures. Newer types of structure are now being developed for use in highly dynamic, harsh marine environments, particularly for renewable energy applications. Therefore, the extent to which mean stresses can enhance corrosion‐assisted fatigue damage in these structures needs to be better understood. A new theoretical model that accounts for mean stress effects on corrosion fatigue crac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…This can be argued considering the investigations that have shown different crack growth behaviour in similar materials with respect to increasing mean stresses . Thorpe et al . found that at free‐corrosion potential, crack growth rates in BS 4360 50D steels were significantly enhanced as the mean stress was increased from 0.5 to 0.7.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This can be argued considering the investigations that have shown different crack growth behaviour in similar materials with respect to increasing mean stresses . Thorpe et al . found that at free‐corrosion potential, crack growth rates in BS 4360 50D steels were significantly enhanced as the mean stress was increased from 0.5 to 0.7.…”
Section: Introductionmentioning
confidence: 99%
“…. Mean stress effects on crack growth rates have been described as the ratio of the minimum to the maximum stresses used for testing . However, it was mentioned by Burnside et al .…”
Section: Introductionmentioning
confidence: 99%
“…Both the strength and mechanism parameters, intersect logC and slope m, are affected. Model estimates and sinusoidal constant amplitude experimental data correlate fairly well (Adepipe et al, 2016).…”
Section: Environmentmentioning
confidence: 57%
“…With respect to the material, loading & response and environment dimensions, mechanical-and electro-chemical properties of the base material, heat affected zone and weld material, frequency, mean and residual stress, humidity and temperature (e.g. Guedes Soares et al 2009;Adepipe et al 2015Adepipe et al , 2016 affect and interact with the corrosion damage process as well. The geometry dimension related typical uniform corrosion induced plate thickness reduction implicitly increases the far field stress level.…”
Section: Complete Strength Criteriamentioning
confidence: 99%